Integração entre tecnologias da plataforma Java EE com o uso de CDI - Merencia, Lucas José (2013)
During the development of an application which uses the Java EE platform, the developer can take advantage of various specifications available on this platform. One of them is CDI, which provides a set of services that when combined may facilitate the development of this kind of application. CDI was initially designed for use with stateful objects, but this technology provides broader uses, allowing the interaction between various components in a flexible manner. Thus, it is possible to use it as an integration layer between the various technologies which the Java EE platform provides, by unifying life cycles and scopes. The present paper aims to demonstrate the main characteristics and features of CDI and how to apply them to provide a layer of integration and unification of some key technologies of the Java EE platform.